Producing a superior genotype from agria potato cultivar using somaclonal variation (Nexo Revista Científica, 2021)
This study was performed to produce a superior genotype from Agria potato cultivar using somaclonal variation. Two leaf and meristem explants in combination with four doses of 2,4-D (0, 2, 3 and 4 mg / l) were used for callus induction in a factorial model based on a completely randomized design with 3 replications. Results showed that the meristem explant, along with 3 mg 2,4-D produced the most suitable calluses. In the mentioned regeneration media, the best calluses were regenerated and one of the regenerated genotypes, which was very different from the parent cultivar was selected. The regenerated genotype, was compared with the maternal genotype (Agria) and a control cultivar (Sante), in a field experiment based on a randomized complete block design with 3 replications. The results showed that in terms of most of the studied traits such as tuber weight per plant, stolon length, percentage of dry matter and percentage of starch, the new genotype was superior, compared to the parent cultivar and in terms of peel percentage and maturity date, the parental cultivar was superior. The results of the molecular comparison also showed that based on CBDP marker, both in terms of band number and band size, there were differences between the new genotype and the parental cultivar. In general, results showed that somaclonal variation can be an effective method to generate new genotypes with superior characteristics.